Factors Influencing Housing Purchase Decisions in Tangerang City, Indonesia During the Covid-19 Period - Johan, Budiman (2023)
This research investigates the intricate dynamics of house purchase decisions in Tangerang City, Banten, Indonesia, with a specific emphasis on the unprecedented challenges posed by the COVID-19 pandemic. Utilizing R-Square (R2) and Predictive Relevance (Q2) analyses, the study aims to comprehensively assess the influence of independent variables on dependent variables, shedding light on the determinants and implications of purchasing decisions during these extraordinary times. The R-Square analysis,facilitated by SmartPLS, discloses that collectively, Ownership Determinants (X1), Service Excellence (X2), and Change in Purchase Intention (X3) account for 12.9% of the variability in Purchase Decisions (Y). The noteworthy finding emphasizes the need for a holistic understanding of factors influencing home purchasing, as the remaining 87.1% is attributed to unexplored constructs. The Predictive Relevance Value Test (Q2) fortifies the model's robustness, with a Q2 value of 0.051 for the Purchase Decision construct, affirming the predictive validity of exogenous variables in anticipating observed values. Hypothesis testing is executed to scrutinize the relationships between variables. The results affirm that Ownership Determinants significantly enhance both Purchase Decisions and Purchase Intentions. Conversely, Service Excellence demonstrates a noteworthy positive impact on Purchase Intentions but exhibits a statistically insignificant negative impact on Purchase Decisions. These empirical findings underscore the pivotal role of Ownership Determinants in shaping purchase intentions and decisions, offering practical insights into the intricacies of the property market during the COVID-19 pandemic. In conclusion, this research enriches our understanding of property market dynamics in the challenging context of the COVID-19 pandemic. The empirical results provide actionable implications for refining marketing strategies, elevating customer experience, and adapting to evolving environmental factors, thereby contributing to more informed policy support.